The potential risk components and prevention measures of the Ebola virus disease outbreak in Liberia: An in-depth interview with the health workers and stakeholders - Moses Tende Stephens; Juniastuti; Sulistiawati; Peter Chilaque Dossen (Belitung Raya Foundation, Indonesia, 2024)
Background: The Ebola virus, a highly infectious and deadly pathogen, has posed a significant public health threat in West Africa for several decades. Liberia is one of the most severely affected countries. Healthcare personnel, including nurses, are on the front lines of patient care, and their perspectives are invaluable in understanding the challenges that arise during outbreaks, especially in implementing prevention measures. Objective: This study aimed to explore the potential risk components and prevention measures of the Ebola virus disease (EVD). Methods: This study used an exploratory descriptive qualitative design. Five stakeholders, ten doctors and five nurses who had suffered from EVD during the outbreak in Liberia participated in semi-structured interviews to provide their experience and comprehensive perspectives on EVD. Data were collected from February 2022-August 2023. NVivo 12 plus was used for inductive thematic analysis. Results: Six themes and several subthemes emerged: 1) transmission modes (body contact, body fluid, sexual intercourse, traditional burial), 2) funeral attendance (traditional practices and crowded gatherings), 3) community-led prevention (promoting good hygiene practices, increasing awareness, contact tracing, and surveillance), 4) Ebola virus vaccine (false sense of security, potential side effects, and limited data), 5) challenges in implementing prevention measures (inadequate health infrastructures, difficulty of tracing infected people, lack of resources, and cultural-social barriers), 6) Liberia’s health systems (a weak, underfunded, fragile health infrastructure, lack of health facilities and shortage of health workers). Conclusion: Several potential risk components contributing to the EVD outbreak should be a public concern. Strengthening the current healthcare system supported by local community and international aid providers (multidisciplinary teams) is needed to anticipate behavioral problems and to improve the efficacy of the prevention measures appropriate to the conditions in Liberia. Accordingly, the nurses’ compliance with the recommended prevention practices is necessary.